The Distribution of Legal Research Topics on Artificial Intelligence: A Bibliometric Study - Muhammad Asrul Maulana; Savira Aristi (International Journal of Artificial Intelligence Research, 2024)
This study aims to determine the distribution of legal research topics related to Artificial Intelligence. This study uses the lens of an indexing institution, to find raw data on the research distribution. The method used is Bibliometric analysis. The results of the research found that this study showed the keywords (Co-Occurrence) were divided into 3 clusters which had a total of 49 topics. Based on the collaboration of authors (Co-Authorship) has 1 cluster which includes 194 authors. Out of a total of 385,943 search results for scientific work, the most prolific author is Wei Wang with 361 documents created by journal articles. Meanwhile, research with the keyword Artificial Intelligence experienced fluctuating developments and the most publications occurred in 2022 with a total of 42,483 publications.